Replanteando la responsabilidad social corporativa a partir de la ejecución de obras por impuestos - Aguirre Alván , Luis Alexander (2023)
Through this article, the author reconsiders the role that mining companies should play, emphasizing corporate social responsibility, and how these companies can collaborate with the development of the communities neighboring their extraction areas through the execution of works by taxes that allow the construction of infrastructure, this via a redirection of the taxes that mining companies must pay to the State, in order to improve access to services and the quality of life of the population.